Analysis of Undergraduate Students' Awareness of Chemical Laboratory Extraction Methods - Khalid Zainulabdeen; Muna Bufaroosha; Raghda Alsayed; Mustafa Abdallh; Marwa Fadhil; Thura Alyasiri; Eamd Yousif (Universitas Negeri Yogyakarta, 2026)
Laboratory education is a key part of undergraduate chemistry programs, linking theoretical concepts with hands-on practice. In this practical context, separation science remains vital; in fact, extraction methods are crucial for various purposes, including pharmaceutical analysis and environmental surveillance. This study presents an academic and professional analysis of questionnaire data collected from undergraduate students regarding their awareness of chemical laboratory extraction methods. The analysis focuses on interpreting responses to each question, identifying potential correlations among students' understanding of different concepts, and supporting these interpretations with relevant academic references.